Navigating choice in the face of uncertainty: using a theory informed qualitative approach to identifying potential patient barriers and enablers to participating in an early phase chimeric antigen receptor T (CAR-T) cell therapy trial - Dean A Fergusson; Manoj M Lalu; Justin Presseau; Kednapa Thavorn; Joshua Montroy; Natasha Kekre; Gisell Castillo; Sarah Asad; Madison Foster; Terry Hawrysh; Harold Atkins; Stuart Schwartz; et al. (BMJ Open)
Objectives Bench to bedside translation of groundbreaking treatments like chimeric antigen receptor T (CAR-T) cell therapy depends on patient participation in early phase trials. Unfortunately, many novel therapies fail to be adequately evaluated due to low recruitment rates, which slows patient access to emerging treatments. Using the Theoretical Domains Framework (TDF), we sought to identify potential patient barriers and enablers to participating in an early phase CAR-T cell therapy trial.Design We used qualitative semistructured interviews to identify potential barriers and enablers to patients’ hypothetical participation in an early phase CAR-T cell therapy trial. We used the TDF and directed content analysis to identify relevant domains based on frequency, relevance and the presence of conflicting beliefs.Participants Canadian adult patients diagnosed with haematological malignancies.Results In total, we interviewed 13 participants (8 women, 5 men). Participants ranged in age from 18 to 73 (median=56) and had been living with haematological cancer from a few months to several years. We found participants were unfamiliar with CAR-T cell therapy but wished to know more about treatment safety, efficacy and trial logistics (domains: knowledge, beliefs about consequences). They were motivated by altruistic considerations, though many prioritised personal health benefits despite recognising the goals (ie, establishing safety) of early phase clinical trials (domains: goals, intentions). Every participant valued receiving medical advice from their haematologists and oncologists, though some preferred impartial medical experts to inform their decision making (domain: social influences). Finally, participants indicated that improving access to financial and social supports would improve their trial participation experience (domain: environmental context and resources).Conclusion Using the TDF allowed us to identify factors that might undermine participation to a CAR-T cell therapy trial and to optimise recruitment processes by considering patient perspectives to taking part in early phase trials.Trial regestration: NCT03765177; Pre-results.